Why is the Common Grackle becoming less common? - Noah P. Horsley; Michael P. Ward (Avian Conservation and Ecology, 2021)
Despite a generalist life history and a widespread distribution, the Common Grackle (Quiscalus quiscula) has declined by more than 58% since 1970. In Illinois, where this study was conducted, the current rate of decline is 7.03% annually. We hypothesized that low reproductive success in intensely agricultural areas is driving population decline. To test this, we quantified the nesting success and post-fledging survival of Common Grackles in central Illinois. Over a 2-year period, we monitored 188 nests and tracked the survival of 53 fledglings. Our estimate for nesting success of 0.622 (95% CI: 0.549-0.695) was much higher than the literature average of 0.267. Similarly, although post-fledging survival had not been estimated previously for Common Grackles, our estimate of 0.617 (95% CI: 0.471-0.764) was relatively high compared to that of other songbirds (range: 0.23-0.87). The most important factor influencing these estimates was ordinal date, which had a negative relationship with both nesting success and post-fledging survival. These results suggest that reproductive success is not the primary driver of population decline in Illinois. To expand upon the field portion of our study, we constructed a demographic model and used it to conduct a global sensitivity analysis. In our model, adult survival was the most influential demographic parameter in the context of population change. This study serves as an initial step in understanding the mechanism(s) of decline in the Common Grackle. We recommend additional research on the survival of Common Grackles, particularly in relation to persecution on the wintering grounds and exposure to agricultural chemicals.